2017
DOI: 10.1007/s40368-017-0271-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dark discolouration and enamel/dentine fracture on the oral health-related quality of life of pre-schoolers

Abstract: Dark discolouration and enamel-dentine fracture without pulp exposure were associated with a negative impact on the life of pre-schoolers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…However, when the trauma affected the enamel-dentin, it had an impact on the quality of life. Similar results were found by Ramos-Jorge et al 24 in the same age group.…”
Section: Discussionsupporting
confidence: 91%
“…However, when the trauma affected the enamel-dentin, it had an impact on the quality of life. Similar results were found by Ramos-Jorge et al 24 in the same age group.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the variables were obtained from a questionnaire sent to the parents. 16 Questions regarding sex, age, school shift, sleep quality, and parents' perception of children's behavior were answered. The school shift referred to the time when the children went to school, i.e., in the morning or in the afternoon.…”
Section: Research Variablesmentioning
confidence: 99%
“…Previous studies showed that subsequent to the dental tissue trauma (e.g., enamel or dentinal fracture), bacterial invasion in the fracture could determine further infection and exposed dentinal tubules can cause pulp inflammation that leads to either repair or necrosis of the pulp [3]. Discoloration of the tooth after trauma can negatively affect the Oral Health related Quality of Life (OHRQoL) of children and adolescents [4, 5]. Also, the monetary costs of immediate and follow-up care to dental trauma patients, their families and oral health services are substantial [6].…”
Section: Introductionmentioning
confidence: 99%